Factors associated with iron nutrition anemia in mothers pregnant at bunda patimah primary clinic: Anemia In Mothers Pregnant - Marlina; Elya Rosa Sembiring (Institute of Computer Science (IOCS), 2023)
Introduction: Pregnancy is the period from conception to the time of birth, counting from the first last menstruation. Based on WHO (World Health Organization) data in 2017, it is estimated that anemia affects 33% of women of reproductive age globally. Objective: The benefit of this research is that pregnant women know the signs of anemia and how to treat it. This study aims to determine the factors associated with the incidence of iron nutrition anemia in pregnant women at the Patimah Primary Clinic in 2020. Method: The research design was an analytic survey with a cross sectional approach. The population in this study were all pregnant women who experienced anemia with anemia, as many as 40 Trimeste III pregnant women at the Primary Clinic Bunda Patimah Medan from December to April 2020 and the sampling technique using the total sampling method. The data obtained by primary data were analyzed by using Chi Square statistical test with p value (0.05). The Result : Based on the results a relationship between knowledge and the incidence of anemia with a p-value of 0.002, there is a relationship between husband's support and the incidence of anemia with a p-value of 0.001, there is a relationship of compliance with taking tablets Fe with anemia incidence with p-value 0.000. Conclusion : It is hoped that health workers at the Mother Patimah Primary Clinic so that this research can be used as a reference for the implementation of treatment and reduce the risk of anemia in pregnant women and as additional knowledge for mothers about factors related to anemia.